The Role of Traditional Medicine in Indonesia’s Healthcare System: A Path to Integrating Cultural Practices and Health Justice (Indonesian Health Justice Review, 2025)
Traditional medicine plays a significant role in the healthcare system of Indonesia, particularly in rural and indigenous communities. This paper explores the challenges and opportunities of integrating traditional medicine into Indonesia’s modern healthcare system in a way that respects cultural practices while promoting health justice. Drawing on qualitative research, including interviews with traditional healers, patients, and healthcare providers, the study investigates the legal, social, and cultural barriers to integrating traditional medicine into formal healthcare policies. The research finds that while traditional medicine is widely trusted and utilized by various communities, it often operates outside the formal health system, limiting its potential to contribute to health justice. Moreover, there are concerns regarding safety, efficacy, and regulation, particularly in terms of ensuring that traditional practices complement, rather than conflict with, evidence-based medical care. The paper advocates for a balanced approach, proposing policies that regulate and integrate traditional healing practices into Indonesia’s healthcare system, ensuring that they meet safety standards and complement the work of modern medical professionals. Recommendations include creating a regulatory framework that acknowledges the value of traditional medicine, training healthcare workers in cultural competence, and promoting research into the benefits of traditional practices for disease prevention and health promotion.